Primary headache in academics: a cross-sectional study - Silva, Lindair Alves da; Carneiro, Ana Lúcia Basilio; Alves, Lincoln Basilio; Ramos, Semírames Cartonilho de Souza; Silva, Iago José Lopes da; Brasil, Arthur Willian de Lima; Sallem, Flávio Augusto Sekeff (Headache Medicine, 2022)
Headache is a frequent, long-standing and universal neurological disorder with high prevalence worldwide. Objective To verify the prevalence of headache and self-medication among healthcare academics. Methods This was a cross-sectional, descriptive and quantitative study, carried out with 165 healthcare academics. A questionnaire was used as a methodological instrument to collect data. Results The academics were mostly female, aged between 18 and 54 years, from the State of Paraiba and single. The lifetime prevalence of headaches was 98.2%. Most volunteers (62.4%) have a probable diagnosis of primary headache. Of these, the most prevalent was migraine, especially with aura, and tension-type headache (TTH). Of the group under analysis, the majority have not had consultations because of the pain and therefore have no medical diagnosis and no treatment. Some treated the pain only in a crisis. Of these, most practiced self-medication, mainly with dipyrone and paracetamol. Stress, worry and sleep deprivation were the most cited factors among those that usually cause pain. Conclusion Clarifications, preventive measures, correct diagnosis and appropriate treatment can reduce the emotional, socioeconomic and academic losses of this frequent neurological complaint among students.